Scottish Medical Imaging Service - Technical and Governance controls. - Jackie Caldwell; Robert Wallace; Carole Morris; Simon Fleming; Rob Baxter; Ruairidh MacLeod; William Kerr; Donald Scobbie; Simon Rogers; Felix Ritchie; Esma Mansouri-Benssassi; Susan Krueger; et al. (International Journal of Population Data Science, 2022)
Objectives The Scottish Medical Imaging (SMI) service provides linkable, population based, “research-ready” real-world medical images for researchers to develop or validate AI algorithms within the Scottish National Safe Haven. The PICTURES research programme is developing novel methods to enhance the SMI service offering through research in cybersecurity and software/data/infrastructure engineering.